Adaptive Action-Based Management Model for Inclusive Early Childhood Education - Rini Triana; Nasir Usman; Niswanto Niswanto (Gawi: Journal of Action Research, 2026)
This study aimed to develop an Adaptive Action-Based Inclusive School Management Model to enhance the efficacy of inclusive early childhood education (ECE) in Banda Aceh, Indonesia. Employing a qualitative school-based action research design across three inclusive ECE institutions, the study involved 13 purposively selected participants, including school principals, educators, special assistant teachers, parents, and an education office representative. The methodology was operationalized through two iterative cycles of planning, action, observation, and reflection, with interventions targeting inclusive management optimization via structured planning, stakeholder coordination, and systemic monitoring. Qualitative data derived from in-depth interviews, participant observation, and document analysis were processed utilizing the interactive qualitative analysis model of Miles, Huberman, and Saldaña, supported by NVivo software. planning practices were collaborative and child-centered but insufficiently documented, implementation was adaptive and outcome-oriented yet weakly coordinated, and evaluation effectively monitored child development but lacked institutional integration. Major constraints included limited government support, infrastructure, and teacher capacity, while adaptive strategies relied on collaboration, communication, and internal initiatives. The study proposes an Adaptive Action-Based Inclusive School Management Model characterized by iterative improvement, collaborative engagement, adaptive decision-making, and outcome-oriented evaluation. The results highlight the importance of strengthening systematic management practices and policy support to ensure sustainable inclusive education.